INSTRUKSI DALAM PENGAJARAN AGAMA ISLAM PADA ANAK BERKEBUTUHAN KHUSUS - Eka Lizahara Saputri; Hasibah (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2025)
This study aims to explore the instruction applied by teachers in learning Islamic religion with children with special needs. Some schools are known to have difficulty implementing individualised Islamic education. This study highlights the importance of an individualised approach and the integration of spiritual values to support the emotional, social and spiritual development of children with disabilities based on Islamic education principles. The research method used a qualitative approach with literature review and descriptive analysis. Data was collected from various sources such as journal articles, books and related research reports from 2018-2024 through the Google Schoolar search engine. The results show that giving proper instructions, such as the use of simple language, varied voice intonation, and reinforcement can increase student engagement and help them achieve learning objectives. The teacher's ability to provide instruction is the key to successful teaching of Islamic Religion. In addition, the implementation of Individualised Learning Programmes (ILEs) provides a solution to meet the unique needs of each student. This study emphasises that developing teachers' competence in understanding the characteristics of children with disabilities is essential to creating an inclusive and supportive learning environment. Holistic and adaptive teaching in Islamic Religious Education not only contributes to the formation of the spirituality of children with disabilities but also provides an important provision for children with disabilities. Translated with DeepL.com (free version)